Properties of Neurons Derived from Induced Pluripotent Stem Cells of Gaucher Disease Type 2 Patient Fibroblasts: Potential Role in Neuropathology - Sun, Ying; Florer, Jane; Mayhew, Christopher N.; Jia, Zhanfeng; Zhao, Zhiying; Xu, Kui; Ran, Huimin; Liou, Benjamin; Zhang, Wujuan; Setchell, Kenneth D. R.; Gu, Jianguo; Grabowski, Gregory A. (PloS one, 2015)
Gaucher disease (GD) is caused by insufficient activity of acid β-glucosidase (GCase) resulting from mutations in GBA1. To understand the pathogenesis of the neuronopathic GD, induced pluripotent stem cells (iPSCs) were generated from fibroblasts isolated from three GD type 2 (GD2) and 2 unaffected (normal and GD carrier) individuals. The iPSCs were converted to neural precursor cells (NPCs) which were further differentiated into neurons. Parental GD2 fibroblasts as well as iPSCs, NPCs, and neurons had similar degrees of GCase deficiency. Lipid analyses showed increases of glucosylsphingosine and glucosylceramide in the GD2 cells. In addition, GD2 neurons showed increased α-synuclein protein compared to control neurons. Whole cell patch-clamping of the GD2 and control iPSCs-derived neurons demonstrated excitation characteristics of neurons, but intriguingly, those from GD2 exhibited consistently less negative resting membrane potentials with various degree of reduction in action potential amplitudes, sodium and potassium currents. Culture of control neurons in the presence of the GCase inhibitor (conduritol B epoxide) recapitulated these findings, providing a functional link between decreased GCase activity in GD and abnormal neuronal electrophysiological properties. To our knowledge, this study is first to report abnormal electrophysiological properties in GD2 iPSC-derived neurons that may underlie the neuropathic phenotype in Gaucher disease.